PENINGKATAN KEAKTIFAN PESERTA DIDIK KELAS V SEKOLAH DASAR DALAM MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Maharani Dyah; Riska Fahmawati; Dewi Suci; Adi Nurcahyo; Rohman; Artik; Edy Heru Prasetyo (Jurnal Genta Mulia, 2025)
This study is based on the problem of low learning activity of students in grade V. This is indicated by a lack of enthusiasm during learning, lack of student interaction, and low participation in answering questions, asking questions, and completing assignments. The research conducted was Classroom Action Research (CAR) to see an increase in student learning activity using the Problem-Based Learning (PBL) model when implementing Pancasila learning in class. The subjects of the study were 22 grade V students of SD Muhammadan Plus Malangjiwan, Colomadu. The indicator of the success of this study is the achievement of the percentage of students’ activeness reaching 75%. CAR is carried out for 2 cycles. The type of data used in this study is qualitative data that includes the results of direct observation, which the researcher observes without being directly involved. In addition, quantitative data is also obtained from the results of processing the presentation of students’ activeness. Data collection is carried out through observation. Through data collection, it can be seen that in cycle I reached 63%, which describe that the results of the students’ activeness were still lacking, then increased in cycle II reaching 70.3%. Based on these results, can describe that the PBL method can increase of students’ activeness in class V students on the Pancasila subject.